PENGELOLAAN ATRAKSI WISATA BUATAN UNTUK MENINGKATKAN MINAT BERKUNJUNG DI SATUPAM TANGERANG SELATAN - Elva Herlim; Ricky Deo Volento Gultom, Cherly Jesslyn Waisa, Manjou Odira, Budi Setiawan (Jurnal Ekonomi dan Bisnis, 2025)
SATUPAM located in South Tangerang is one of the artificial tourist destinations that has the potential to continue to be developed to increase tourist interest. This study aims to examine the management of artificial tourist attractions in increasing interest in visiting SATUPAM, South Tangerang. Artificial tourism is one of the leading attractions in the development of a tourist village. Then the method used in collecting data in this journal, namely the qualitative method with observation and interview techniques. The main resource person in this study is the manager of the SATUPAM tourist area to identify strengths, weaknesses, opportunities and threats. Based on the results of observations and interviews conducted in the SATUPAM tourist village, it has artificial and natural attractions in it that can be used as artificial tourist attractions. Starting from the catfish farm which is a characteristic or uniqueness of the tourist village and nature that can be used as a painting attraction. With proper management, this tourist village can have great potential to become a leading artificial tourist attraction and increase tourist visits to South Tangerang.